PENGAWASAN KINERJA PEGAWAI DIPERUSAHAAN DAERAH RUMAH POTONG HEWAN KOTA MAKASSAR - Nurmayanti, Nurmayanti; Mahsyar, Abdul; Said, Alimuddin (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
This research aimed to know the direct  and indirect control wich have been done by a company employee of a slaughterhouse Makassar city in managing slaughters house in Makassar city. The type of this research is qualitative research by describing the form of the direct  and indirect control performance employees. This kind of research is phenomenologycal research. In collecting data, the researcher use observation, interview, and documentation technique. Data analysis technique use data reduction, data presentation, and conclusion. To determine the validity of the data used triangulation technique, time triangulation, and source triangulation. The results of this research was  indicate that direct and indirect control by employees of local companies slaughterhouse of Makassar city in managing slaughterhouses conciderate that employees performance has not been maximized, the researcher still found productive female animals and  animals died that are not slaughtere, and the slaughterhouses is uncleanliness and it hygiene are also not found.  Keywords: controlling performance,employees